An algebra problem by Rama Devi

Algebra Level 3

Find the remainder when x 1999 x^{1999} is divided by x 2 1 x^2 -1 .

2 0 1 x x x 2 x^2

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Rama Devi
Jul 24, 2015

By division Algorithm ,

Dividend = (Divisor * Quotient) + Remainder.

From the problem , we know that Dividend is x 1999 x^{1999} , Divisor is x 2 1 x^2 - 1

We know that the degree of the remainder is always one less than the degree of the Divisor .Since the degree of the Divisor is 2, the degree of the remainder is 1 , which is in the form a x + b ax+b .

Dividend = (Divisor * Quotient) + Remainder.

x 1999 x^{1999} = ( x 2 1 x^2 - 1 ) * Q Q + a x + b ax+b

x 1999 x^{1999} = ( x + 1 ) ( x 1 ) (x+1)(x-1) * Q Q + a x + b ax+b

Now put x = 1 x = 1

1 1999 1^{1999} = 0 0 + a + b a+b

a + b a + b = 1 1 .............................................................. 1 \boxed{1}

Now put x = 1 x=-1

1 1999 {-1}^{1999} = 0 0 + b a b-a .

b a b - a = 1 -1 ............................................................ 2 \boxed{2}

From 1 \boxed{1} and 2 \boxed{2} , We get the values of a a and b b as a = 1 a=1 and b = 0 b=0 .

Therefore the remainder is a x + b ax+b , which is 1 ( x ) + 0 1(x)+0 , which is x x

Therefore the required answer is x \boxed{x}

Great solution

Sai Ram - 5 years, 10 months ago
Abhijeet Verma
Jul 25, 2015

I think a shorter solution is- x 2 = 1 x^{2}=1 therefore, x 1999 = x 1998 . x = x x^{1999}=x^{1998}.x=x

My approach is standard

Rama Devi - 5 years, 10 months ago
Chew-Seong Cheong
Jul 25, 2015

Consider the following:

\(\begin{array} {} \color{blue}{\dfrac{x^3}{x^2-1}} = \dfrac {x^3-x+x}{x^2-1} = x + \dfrac{x}{x^2-1} & \Rightarrow \text{remainder} = x \\ \color{red}{\dfrac{x^5}{x^2-1}} = \dfrac {x^5-x^3+x^3}{x^2-1} = x^3 + \color{blue}{\dfrac{x^3}{x^2-1}} & \Rightarrow \text{remainder} = x \\ \dfrac{x^7}{x^2-1} = \dfrac {x^7-x^5+x^5}{x^2-1} = x^5 + \color{red}{\dfrac{x^5}{x^2-1}} & \Rightarrow \text{remainder} = x \\ \Rightarrow \dfrac{x^{1999}}{x^2-1} & \Rightarrow \text{remainder} = \boxed{x} \end{array} \)

Moderator note:

This is not correct. What relationship you have between the first three lines and the last line?

汶良 林
Aug 8, 2015

x 1999 = x 1999 x + x x^{1999} = x^{1999} - x + x

= x ( x 1998 1 ) + x = x(x^{1998} - 1) + x

= x ( x 2 1 ) Q ( x ) + x = x(x^{2} - 1)Q(x) + x

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...